Stand and Deliver : How to Become a Masterful Communicator and Public Speaker - Training, Dale Carnegie (London Simon & Schuster, 2012)
Uncover the prized communication secrets of Politicians, CEOs, and successful people everywhere!
Keywords: Public speaking -- Persuasion (Rhetoric)